Women under Patriarchy: A Postcolonial Feminist Critique of Wole Soyinka’s The Lion and the Jewel - Adhikary, Ramesh Prasad (European Scientific Journal, ESJ, 2020)
This research paper is focused on the exploration of female exploitation in Wole Soyinka’s The Lion and the Jewel in the context of postcolonial Nigeria. This paper tries to explore how Wole Soyinka posits postcolonial and feminist rebellion in his play. It explores female suppression and also depicts the failure of postcolonial and feminist resistance to colonial principles. Like colonialists, postcolonialists and feminists overlook the different kinds of injustice and harassments women undergo in the non- Western world, which is also called the Third World. The text also shows how the female suppression and exploitation continues even after the abolition of colonial rule in Nigeria. The researcher has taken the text The Lion and The Jewel of Soyinka as a primary source of data for the qualitative research; and the postcolonial feminism has been used as a theoretical tool for the analysis of the text.